Antifungal properties of selected plants of Apocynaceae family against the human fungal pathogen Candida albicans - Wankhede, Savita Bajrang; Routh, Madhushree Madhumita; Rajput, Sandeep Balsingh; Karuppayil, Sankuny Mohan (International Current Pharmaceutical Journal, 2013)
The ethnobotanical evaluation of plant based chemicals has proven themselves greatly in last few decades. Plants have been a rich source of therapeutic agents and form the basis of traditional medicine system. On the basis of this, in vitro antifungal activities of extracts of Catharanthus roseus, Nerium oleander and Taberenemontana divaricata leaf extracts were evaluated in the present study by 96 well microtiter plate assays using human fungal pathogen Candida albicans ATCC90028 strain. The activity was measured by spectophotometric methods to determine the Minimum Inhibitory Concentration (MIC). The Minimum Fungicidal Concentrations (MFC) for the extracts was also determined by a plate assay. The distilled water extract, petroleum ether extract, methanolic extract, ethyl acetate extract and sequential distilled water leaf extracts of all the plants showed potential activity against C. albicans ATCC 90028. The study ascertains the value of Apocynaceae plants, which could be of considerable interest to the development of new safer antifungals. DOI: http://dx.doi.org/10.3329/icpj.v2i7.15155 International Current Pharmaceutical Journal, June 2013, 2(7): 122-125